Pengembangan Media berbasis Web (Virtual Map) sebagai Inovasi Media di SD - Susilo Tri Widodo; Mahmud Rafi Al Ghani (Universitas Pendidikan Indonesia (UPI), 2017)
This research aims to develop web based media (virtual map) on the civic education learning of NKRI materials on fifth-grade. This type of research is Research and Development (RD). The procedure of this research is analysis, design, manufacture, testing, and maintenance. The subject of study was fifth-grade students in Wonorejo Elementary School. Data collection using interview, tests, questionnaires, and documents. Data were analyzed using descriptive analysis consist central tendency and varians analysis. The results showed that virtual map fit for use with a score of the media percentage assessment 88% and a score of the content’s material components 100%. Media test results showed an average increase equal to 29,57%. Percentage mastery increased from 35.71% to 42.82%. Conclusion in this study is the media virtual map effectively used in learning civic education of NKRI materials.